(untitled) (Research, Society and Development, 2023)
Sturge-Weber Syndrome is a phacomatosis with incidence of 1:20,000-50,000 live births and is related to the presence of facial Port Wine Stain birthmark. Vascular changes generated by a mutation of the GNAQ gene cause cutaneous, cerebral and ocular involvement. The main neurologic symptom is epilepsy, which usually appears before 2 years of age. Seizures may be of difficult control and are associated with hemiparesis, intellectual impairment and behavioral changes, mainly when they start before 6 months of age. This is an integrative review with the objective of analyze scientific literature on neuroradiological methods indicated to diagnose leptomeningeal angioma in children with risk factors for this syndrome. There were selected 34 articles between the ones found at MEDLINE and LILACS databases. From them, it was found that the MRI is still the choice method for initial diagnosis, while the CT has no recommendation at this moment and should be reserved to emergencies. Functional studies are preferable for surgery evaluation and ultrasonographic methods are promising when other methods are not disponible and for pharmacological treatment monitoring.